Peripheral Organ Equivalent Dose Estimation Procedure in Proton Therapy - Domingo, Carles; Lagares, Juan Ignacio; Romero-Expósito, Maite; Sánchez-Nieto, Beatriz; Nieto-Camero, Jaime J.; Terrón, Jose Antonio; Irazola, Leticia; Dasu, Alexandru; Sánchez-Doblado, Francisco (Frontiers in Oncology, 2022)
The aim of the work is to present a reproducible methodology for the evaluation of total equivalent doses in organs in proton therapy facilities. The methodology is based on measuring dose equivalent in representative locations inside an anthropomorphic phantom where photon and neutron dosimeters could be inserted. Monte Carlo simulation is needed for obtaining neutron energy distribution inside the phantom. The methodology was implemented for a head irradiation in the passive proton beam of iThemba Labs (South Africa). TLD600 and TLD700 pairs were used as dosemeters inside the phantom and GEANT code for simulations. In addition, Bonner sphere spectrometry was performed inside the treatment room to obtain the neutron spectra, together with relevant neutron dosimetric quantities per treatment Gray and percent contribution to neutron fluence and ambient dose equivalent in four energy groups, at two locations. The neutron spectrum at one of the locations was also simulated, so that reasonable agreement between simulation and measurement allowed validation of the simulation. Results showed that total out-of-field dose equivalent inside the phantom ranged from 1.4 to 0.28 mSv/Gy, due mainly to the neutron contribution and with a small contribution from photons, 10% on average. The order of magnitude of equivalent dose in organs was similar, displaying a slow reduction in values as the organ is farther from the target volume. These values are in agreement with those found by other authors in other passive beam facilities under similar irradiation and measurement conditions.